In vitro antioxidant studies of Sitopaladi Churna, a polyherbal Ayurvedic formulation - Makhija, Inder Kumar; Ram, H. N. Aswatha; Shreedhara, C. S.; S, Vijay Kumar; Devkar, Raviraj (Free Radicals and Antioxidants)
Introduction: “Sitopaladi churna” is a reputed Ayurvedic polyherbal medicine prescribed for pleurodynia, intercostal neuralgia, cough associated with bronchitis, supportive agent for allergy, viral respiratory infection, and in pharyngeal and chest congestion. Antioxidants play an important role in protecting cellular damage by reactive oxygen species. Plants containing phenolic compounds have been reported to possess strong antioxidant properties. Methods: Antioxidant potential of the Sitopaladi churna was studied using different in vitro free radical models like DPPH, ABTS, nitric oxide and superoxide scavenging radical models. Results: The extracts showed good dose dependent free radical scavenging property in all the models. IC50 values of methanolic and aqueous extracts of Sitopaladi churna were found to be 65.6 and 44.88 μg/ml for DPPH, 74.5 and 66.46 μg/ml for ABTS, 191.77 and 170.15 μg/ml for nitric oxide, 94.79 and 62.03 μg/ ml for superoxide radical, respectively. Total phenolic contents of aqueous and methanolic extract were found to be 256.25 and 298.2 μg equivalent of gallic acid. Conclusions: The antioxidant potential may be directly linked to the phenolic compounds present in the ingredients of Sitopaladi churna. The data obtained in this study suggest a possible use of Sitopaladi churna as a natural antioxidant agent.
Keywords: Free radicals; antioxidant; Sitopaladi churna; phenolic compounds